The SARS-CoV-2 B.1.351 Variant Can Transmit in Rats But Not in Mice - Zhang, Cheng; Cui, Huan; Li, Entao; Guo, Zhendong; Wang, Tiecheng; Yan, Fang; Liu, Lina; Li, Yuanguo; Chen, Di; Meng, Keyin; Li, Nan; Qin, Chengfeng; et al. (Frontiers in Immunology, 2022)
Previous studies have shown that the B.1.351 and other variants extend the host of SARS-CoV-2 to mice. However, no evidence of natural transmission of SARS-CoV-2 in wild mice is documented to date. Here we evaluated the replication and contact transmission of the B.1.351 variant in mice and rats. The B.1.351 variant could infect and replicate efficiently in the airways of mice and rats. Furthermore, the B.1.351 variant could not be transmitted in BALB/c and C57 mice, but could be transmitted in rats by direct contact with moderate efficiency. Additionally, the B.1.351 variant did not transmit from the inoculated Syrian hamsters to BALB/c mice. In summary, the risk of the B.1.351 variant transmission in mice is extremely low, but the transmission risk in rats should not be neglected. We should pay more attention to the potential natural transmission of SARS-CoV-2 variants in rats and its possible spillback to humans.